Desenvolvimento de vacina multiepítopo e análise de potenciais inibidores da protease Mpro do Sars-CoV-2 via vacinologia reversa e bioquímica computacional - Campos, Daniel Melo de Oliveira (2024)
Infections caused by SARS-CoV-2 have posed a significant threat to global public health and remain a relevant and complex issue. This thesis aimed to explore new approaches to combat the virus, focusing on the development of a multi-epitope vaccine and the identification of potential inhibitors of the Mpro protease. Two in silico studies were conducted: one dedicated to designing a multi-epitope vaccine using reverse vaccinology, and the other aimed at analyzing non-covalent inhibitors through computational chemistry. The first chapter of this thesis presents an in silico study for the development of a new multi-epitope vaccine against SARS-CoV-2, including the Alpha, Beta, Gamma, Delta, and Omicron variants. An immunoinformatics approach was used to identify the best immunogenic epitopes from the four structural proteins of the virus (S, M, N, and E) from 475 sequenced genomes from regions with a high incidence of the disease. The vaccine was modeled, refined, validated, and its molecular docking with the TLR3 receptor was evaluated. The results suggest that the candidate vaccine enhances the antibody response and should be tested in clinical trials. In the second chapter, we comparatively evaluated the non-covalent inhibitors WU-04 and ML188 using quantum energy calculations, quantum chemical descriptors, and ADMET predictions to determine their therapeutic potential. We identified that WU04, although more reactive and less stable than ML188, showed greater affinity for Mpro due to more hydrogen and hydrophobic interactions, especially with residues Met165, Asn142, Glu166, His41, and Leu141. The total energy calculated for the MproWU-04 complex was (-52.21 kcal/mol), while for Mpro-ML188 it was (-40.47 kcal/mol), indicating that the WU-04 inhibitor has a higher energetic affinity, contributed by the presence of one more aromatic ring in region i. The substitution of the pyridine ring in region i for another aromatic ring of both potential inhibitors was suggested to improve affinity and eliminate repulsion with His163. Both compounds exhibited good absorption and distribution profiles and low clinical toxicity, but both face challenges regarding half-life, and WU-04 has a high molecular weight. The integration of ADMET analysis and quantum chemical descriptors revealed the need for structural adjustments and possible co-administrations to optimize the clinical efficacy of the inhibitors.